Perspektif Diplomasi Perdamaian Vatikan Pada Konflik Wilayah - Korniawan, Rostamaji (Universitas Komputer Indonesia, 2024)
The peace process of regional dispute is handled with various processes and the sides who are concerned about the conflict, including the Vatican’s aid by using its peace diplomacy. The Vatican knew that mitigating the regional dispute had to face several challenges. However, the process and efforts to mitigate many areas of regional dispute are still the Vatican’s belief that peace becomes part of human rights and universal values. By observing methods based on the issue of regional dispute, this paper purposed to analyze the Vatican’s peace diplomacy during Pope Francis’ leadership. The analysis finds that mitigating regional disputes using a religious approach and the role of the Catholic church and Supreme Pontiff can effectively rehabilitate the conflict and finally turn into expected results based on negotiation. However, the Ukraine-Rusia dispute still creates brain-drain for the Vatican, including several regional disputes in Asian territory. The unresolved dispute indicates that the religious approach still needs aid from the other side. Therefore, the Pope, the Catholic church, and the rest of the world are still using proper diplomacy and strategy to fulfill the goal of the future of global peace.